Conceptional design of photoneutralization test system for negative ion-based neutral beam injection - Hui-hui Hong; Li-zhen Liang; Yuan-lai Xie; Qian-xu Wang; Zhuo Pan; Yao Jiang (Nuclear Engineering and Technology)
Neutral beam injection is one of the effective heating methods in the field of magnetic confinement fusion, and neutralization is the most crucial link in the case of negative ions. To further increase the neutral beam injection power, improve the long pulse operation capability, and optimize the efficiency of the NNBI system, further research and verification about the neutralization mode are needed. Theoretically, photoneutralization can achieve more than 90 % neutralization efficiency. However, maintaining stable operation of the megawatt laser cavity over extended periods poses corresponding challenges. Additionally, the cost associated with laser target surpasses the benefit gained from increased neutralization efficiency, leading to its lack of practical application thus far. This paper proposes a solution to these issues by designing a single-channel, multi-fold photoneutralization verification system utilizing the CRAFT NNBI one-quarter and one-half size negative source test equipment. An outline of the system's test and diagnostics approach is provided. Key parameters such as laser target thickness, negative ion energy, beam shape and efficiency of the photoneutralization system are numerically calculated. Combined with the experimental data of the negative source test platform, theoretical calculations show that the neutralization efficiency can achieve 63 % with the system efficiency exceeding 40 %. Even by increasing the incident laser power or the number of reflections, neutralization efficiency can be increased to 95 %, with a simultaneous increase in system efficiency to 60 %. Maintaining efficiency while increasing incident laser power could reduce the number of reflections to approximately ten, reaching an acceptable threshold. However, this adjustment will increase the irradiation density of a single mirror from 660W/mm2 increases to 3000W/mm2. This paper methodically designs a practical laser neutralization verification platform, which is expected to substantially improve the neutralization efficiency, and facilitate practical application and validation.